Characterisation of Neem and Jatropha Curcas Oils and their Blends with Kerosene for Combustion in Liquid Bio Fuels Cooking Stoves - A. Shanono, Adamu; S. Diso, Ibraheem; Garba, Isa (Journal of Technology Innovations in Renewable Energy, 2017)
The characterisation of raw vegetable oils of neem and jatropha curcas seeds was experimentally carried out in order to obtain requisite data for the design process of liquid bio fuels cooking stoves. Properties of nineteen vegetable oils/kerosene blends including the kerosene sample were also experimentally determined for the purpose of testing the designed and developed bio stoves that utilised these fuel/oils blends as fuels. Results of the characterisation revealed that the kinematic viscosity of jatropha oil (57.6 mm2/s) was 36 times more than the viscosity of the kerosene sample (1.6 mm2/s). On the other hand, the viscosity of neem oil (62.6 mm2/s) was 39 times greater than that of the kerosene sample. In addition, the density of jatropha curcas oil (860 kg/m3) was more than that of the kerosene (760 kg/m3) by 13.16%, while the density of neem oil (890 kg/m3) exceeded that of kerosene sample by 17.11%; all the tests were conducted at 30oC. Meanwhile, the acid number values of jatropha (1.2 mg KOH/g) and neem (3.1 mg KOH/g) oils did not meet the ASTM D6751 acid number standard specification, and only jatropha curcas oil satisfied the DIN 51605 specification. Blending of the oils with kerosene ensured that all the kerosene/jatropha oil blends met the DIN 51605 specification, however only six kerosene/neem oil blends (10% to 60% concentrations) satisfied the requirement. Moreover, among all the kerosene/oils blends, only the 10% and 20% jatropha and 10% neem oils concentrations in the blends met the ASTM D6751 standard acid number specification.